Mechanistic insight into the attenuation of gouty inflammation by Taiwanese green propolis via inhibition of the NLRP3 inflammasome - Hsieh, Chih‐Yu; Li, Lan‐Hui; Rao, Yerra Koteswara; Ju, Tz‐Chuen; Nai, Yu‐Shin; Chen, Yue‐Wen; Hua, Kuo‐Feng (Journal of cellular physiology, 2019)
Dysregulation of NACHT, LRR, and PYD domains‐containing protein 3 (NLRP3) inflammasome is involved in many chronic inflammatory diseases, including gouty arthritis. Activation of the NLRP3 inflammasome requires priming and activation signals: the priming signal controls the expression of NLRP3 and interleukin (IL)‐1β precursor (proIL‐1β), while the activation signal leads to the assembly of the NLRP3 inflammasome and to caspase‐1 activation. Here, we reported the effects of the alcoholic extract of Taiwanese green propolis (TGP) on the NLRP3 inflammasome in vitro and in vivo. TGP inhibited proIL‐1β expression by reducing nuclear factor kappa B activation and reactive oxygen species (ROS) production in lipopolysaccharide‐activated macrophages. Additionally, TGP also suppressed the activation signal by reducing mitochondrial damage, ROS production, lysosomal rupture, c‐Jun N‐terminal kinases 1/2 phosphorylation and apoptosis‐associated speck‐like protein oligomerization. Furthermore, we found that TGP inhibited the NLRP3 inflammasome partially via autophagy induction. In the in vivo mouse model of uric acid crystal‐induced peritonitis, TGP attenuated the peritoneal recruitment of neutrophils, and the levels of IL‐1β, active caspase‐1, IL‐6 and monocyte chemoattractant protein‐1 in lavage ﬂuids. As a proof of principle, in this study, we purified a known compound, propolin G, from TGP and identified this compound as a potential inhibitor of the NLRP3 inflammasome. Our results indicated that TGP might be useful for ameliorating gouty inflammation via inhibition of the NLRP3 inflammasome. Taiwanese green propolis inhibited NLRP3 inflammasome through (1) reducing LPS‐mediated NLRP3 and proIL‐1β expression by NF‐κB downregulation; (2) reducing MSU‐mediated caspase‐1 activation by preserving mitochondrial integrity and inhibiting lysomal rupture; (3) augmenting autophagy.